2019
DOI: 10.1186/s12872-019-1230-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete versus simplified Selvester QRS score for infarct severity assessment in ST-elevation myocardial infarction

Abstract: BackgroundComplete and simplified Selvester QRS score have been proposed as valuable clinical tool for estimating myocardial damage in patients with ST-elevation myocardial infarction (STEMI). We sought to comprehensively compare both scoring systems for the prediction of myocardial and microvascular injury assessed by cardiac magnetic resonance (CMR) imaging in patients with acute STEMI.MethodsIn this prospective observational study, 201 revascularized STEMI patients were included. Electrocardiography was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…We could demonstrate a significant positive correlation between the DETERMINE score and IS. Furthermore, the DETERMINE score remained independently associated with IS even after adjustment for other parameters such as Selvester score, a complex ECG score that has been proposed previously for IS estimation, 9 as well as established clinical parameters such as hs-cTnT, hs-CRP, NT-proBNP, TIMI flow pre-interventional, and post-interventional PCI and anterior infarct localisation. Moreover, we observed a significant and independent association of the DETERMINE score with MVO, a severe marker of reperfusion injury with major prognostic implications in patients with STEMI.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…We could demonstrate a significant positive correlation between the DETERMINE score and IS. Furthermore, the DETERMINE score remained independently associated with IS even after adjustment for other parameters such as Selvester score, a complex ECG score that has been proposed previously for IS estimation, 9 as well as established clinical parameters such as hs-cTnT, hs-CRP, NT-proBNP, TIMI flow pre-interventional, and post-interventional PCI and anterior infarct localisation. Moreover, we observed a significant and independent association of the DETERMINE score with MVO, a severe marker of reperfusion injury with major prognostic implications in patients with STEMI.…”
Section: Discussionmentioning
confidence: 77%
“… 18 19 Especially the modified Selvester QRS score, a 37-criteria/29-points ECG scoring system, has been suggested for IS assessment. 9 20 However, it has recently been shown that the Selvester QRS score only has moderate association to CMR-determined IS. 9 Moreover, due to the numerous criteria that have to be fulfilled for the Selvester score, this score is hardly applicable in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations